Exopolysaccharide from the liquid culture of Ganoderma lucidum as feed additive for red hybrid tilapia (Oreochromis sp.) / Jaganath Puvanen Thiran - Jaganath Puvanen , Thiran (2020)
Feed additive plays a significant role in sustaining fish production. Exopolysaccharide (EPS) obtained from the fermented mycelium of Ganoderma lucidum produced by using submerged-liquid fermentation (SLF) was proposed as a feed additive in this study for red hybrid tilapia (Oreochromis sp.). Body composition, organosomatic indices, and haematological parameters were observed in fish fed with three different diets supplemented with EPS (1 g/kg, 2 g/kg, and 3 g/kg). Although higher concentration EPS feed was observed to produce minor effect on body composition and organosomatic indices, significant effect on both parameters was observed in fish fed with 1 g/kg diet. All diets showed condition factor (CF) values of above 1.4, indicating good fish health and isometric growth. Furthermore, the blood analysis of EPS-treated red hybrid tilapia showed that haemoglobin (HGB: 7.43 g/dl), haematocrit (HCT: 37.50 %), and red blood cell (RBC: 2.69 106/mm3) were significantly increased (P<0.05) at 3 g/kg while the white blood cell (WBC: 176.65 103/mm3) and mean corpuscular haemoglobin concentration (MCHC: 198.50 g/L) were numerically high at 3 g/kg. These findings showed that high EPS supplemented diet could enhance the health status of fish by boosting its immunity. However, the diet supplemented with 1 g/kg is sufficient in contributing to the nutritional value of fillet and improving the health status of red hybrid tilapia, which is suitable for fish farming.